2007
DOI: 10.1002/mrm.21289
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of blood–spinal cord barrier disruption in mice with experimental autoimmune encephalomyelitis

Abstract: Inflammation, demyelination, and blood-spinal cord barrier (BSB) breakdown occur in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. The purpose of this study was to evaluate the utility of MRI for detecting lesions and BSB disruption in vivo during EAE in the mouse lumbar spinal cord, to determine how MR features of BSB disruption change during the course of disease, and to relate such changes to clinical signs and histological features of disease. Following induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 30 publications
4
45
0
Order By: Relevance
“…In the EAE SJL mouse model, it was proposed that the first occurrence of BBB disruption and rabbit IgG leakage occurred in the cerebellum, and then spread to the spinal cord (9). Magnetic resonance imaging in the mouse revealed that BSCB and BBB disruption took place as animals were already displaying acute motor symptoms (10,12). In the brain of EAE mice, Floris et al (10) further observed that monocyte infiltration preceded vascular leakage, although assessments of BBB integrity and cellular infiltration were performed in separate animals that were sacrificed at the end of the imaging session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EAE SJL mouse model, it was proposed that the first occurrence of BBB disruption and rabbit IgG leakage occurred in the cerebellum, and then spread to the spinal cord (9). Magnetic resonance imaging in the mouse revealed that BSCB and BBB disruption took place as animals were already displaying acute motor symptoms (10,12). In the brain of EAE mice, Floris et al (10) further observed that monocyte infiltration preceded vascular leakage, although assessments of BBB integrity and cellular infiltration were performed in separate animals that were sacrificed at the end of the imaging session.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to immune cell invasion, formation of demyelinated lesions, and axonal damage (4,(6)(7)(8). Early breakdown of the BSCB in EAE has been widely documented, but the precise timing and triggers of this disruption are still a matter of debate (9)(10)(11)(12). This has prompted us to look further into the kinetics of BSCB disruption and the putative cellular candidates involved in this process.…”
mentioning
confidence: 99%
“…While large molecule permeability is dependent on transcytosis, we questioned the permeability of small molecules that normally depend on processes such as diffusion. The blood-spinal cord barrier is normally impermeable to magnetic resonance (MR) contrast agents such as the small (260Da) Gadolinium-DTPA reagent, but in cases of barrier disruption will appear hyperintense in T1-weighted MR images (36). MRI detected CNS edema sensitively but almost equally during EAE in B6 and in protected TRPV1 -/-mice, identifying a shared inflammatory element that is, however, self-limiting and without progressive tissue damage in the absence of TRPV1 ( Figure 6F).…”
Section: Bscb and Bbb Collapse In Eae Is Trpv1-dependent And Requiresmentioning
confidence: 99%
“…In the experimental allergic encephalomyelitis model of multiple sclerosis, contrast changes have been observed in conventional anatomic images (Schellenberg et al, 2007), axial diffusivity has been correlated with axonal damage (Budde et al, 2008;Budde et al, 2007;Budde et al, 2009), and decreased quantitative T2 and magnetic transfer values have been shown (McCreary et al, 2009). Numerous studies have also assessed white matter integrity in mouse models of spinal cord injury, using diffusion tensor imaging Kim et al, 2010;Loy et al, 2007;Tu et al, 2010), T1-and T2-weighted imaging (Gonzalez-Lara et al, 2009;Levene et al, 2008;Nishi et al, 2007), and MRM (Bilgen, 2007).…”
Section: Introductionmentioning
confidence: 99%